Cultural Heritage and Local Development: Case of Dida (Southwestern of the Republic of Côte d’Ivoire) for Promoting Sustainable and Inclusive Development - Gninin Aicha Toure; Irie Maxime Goeti Bi; Barpougouni Mardjoua (European Scientific Journal, ESJ, 2026)
Established between the 15th and 18th centuries in present-day Côte d’Ivoire, the Dida community has greatly contributed to the enrichment of Ivorian cultural heritage through its language, traditional attire, craftsmanship, and ancestral social practices, sources of national identity. However, although they hold strong potential for development, this body of knowledge and cultural wealth is now seriously threatened with disappearance. The objective of this study is to highlight the contribution of Dida cultural heritage to sustainable and inclusive local development. The adopted methodology combines documentary research, field surveys, and participation in a cultural festival, an integrated approach that made it possible to inventory Dida heritage and assess its role in sustainable and inclusive local development. The results show that Didaland possesses a rich cultural heritage, combining material culture, intangible heritage, and natural heritage of high ecological and spiritual value. The protection and enhancement of this heritage contribute to the local economy, strengthen community identity, and promote sustainable and inclusive development.